Safety reassessment of cinobufotalin injection: new findings into cardiotoxicity. Issue 4 (12th June 2020) - Li, Min; Wang, Xijie; Qiu, Yunliang; Zhang, Yizhe; Pan, Xueying; Tang, Naping; Chen, Tao; Ruan, Bing; Shao, Shuming; He, Liang; Li, Hua; Ma, Jing
Abstract: Cinobufotalin injection, a traditional Chinese medicine preparation, successfully used for several years, might induce cardiotoxicity. The aim of the study was to evaluate the cardiotoxicity of cinobufotalin injection and the cardiotoxicity-preventive effect of sodium phenytoin in vivo . According to the 4 × 4 Latin square design, four Beagle dogs were allocated into four dose levels of 0, 0.3, 1, and 3 g/kg in treatment phases I–IV (cinobufotalin injection) and 3 g/kg in treatment phase V (cardiotoxicity antidote). The following parameters and endpoints were assessed: clinical observations, body weight, indicators of myocardial injury, and electrocardiogram (ECG) parameters. The cinobufotalin injection-related changes were observed in clinical observations (rapid breathing pattern), indicators of myocardial injury (increased cardiac troponin I, creatine kinase isoenzymes, and aspartate aminotransferase), and ECG graphics (arrhythmia) at 3 g/kg concentration in treatment phases I–IV. The cardiotoxicity of cinobufotalin injection was attenuated by sodium phenytoin in treatment phase V. The results confirmed the cardiotoxicity of cinobufotalin injection, and they might bring information about the appropriate monitoring time points and cardiotoxicity parameters in clinical practices and shed light on the treatment of cardiovascular adverse reactions.